Surface modification of TiAl alloy via current heating technique - Chatdanai Boonruang (2018)
Surface of Ti-52 at% Al alloy was modified via current heating technique. The Ti-52 at% Al alloy with 20 mm diameter × 1.5 mm thick disks was placed in graphitic powder in a glass tube and pressed against it. During the coating process, the direct current was applied across the samples at electrical power of 100-200 W for 10 min. By using X-ray diffraction (XRD), TiC was detected on the alloy treated at 180 W and above. Scanning electron microscopy (SEM) micrographs show the different morphologies, after treatment under different conditions. Energy dispersive X-ray spectroscopy (EDS), SEM and hardness tester show that the carbon concentration, particle size, void size and the hardness of the alloy were increased with the increasing of the applying electrical power, due to the formation of the carbide on the alloy surface. © 2009 Elsevier B.V. All rights reserved.